Pengaruh Social Media Marketing dan Brand Awareness terhadap Niat Beli Produk di Restoran Fast Food - Sholawati, Rochmatin Lailatis; Tiarawati, Monika (Jurnal Ilmu Manajemen, 2022)
This study aims to determine the influence of social media marketing and brand awareness on the purchase intention of fast-food restaurant products. The type of research used is quantitative, using the random sampling method. The number of samples used was 200 respondents. The data collection technique was carried out using an online questionnaire distributed through social media, Whatsapp and Instagram. The data analysis technique is multiple linear regression using SPSS software to test whether social media marketing and brand awareness affect purchase intentions. The results show that social media marketing and brand awareness had a positional effect on the purchase intention of KFC products in Surabaya. Social media marketing and brand awareness also simultaneously affect the purchase intention of fast-food restaurant products. Furthermore, fast food restaurant products are recommended to optimize marketing through social media for all products and introduce fast food restaurant products to grow public brand awareness. Marketing through social media is one of the best marketing strategies amidst the increasing level of digital literacy in society.